2019
DOI: 10.1186/s12889-019-6891-1
|View full text |Cite
|
Sign up to set email alerts
|

The relative impact of smoking, alcohol use and drug use on general sickness absence among Norwegian employees

Abstract: Background It is well documented that tobacco, alcohol and drug use can be detrimental to health. However, little is known about the relative impact of these factors on sickness absence, and whether the association between use of these substances and sickness absence is different for women and men. The aim of this study was to examine the association between tobacco-, alcohol- and drug use, as well as polydrug use, and sickness absence among Norwegian employees. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…The lack of association between alcohol-related problems and sick leave is at odd with prior literature showing an alcohol-sick leave association, both among Norwegian employees ( 19 , 22 , 23 , 29 ) and other populations ( 28 , 30 36 ). However, our results are in agreement with other studies reporting no alcohol-sick leave association ( 39 42 ), including studies from Norway ( 39 , 40 ). Overall, our study did not contribute to clarify the relationship between alcohol consumption and sick leave.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lack of association between alcohol-related problems and sick leave is at odd with prior literature showing an alcohol-sick leave association, both among Norwegian employees ( 19 , 22 , 23 , 29 ) and other populations ( 28 , 30 36 ). However, our results are in agreement with other studies reporting no alcohol-sick leave association ( 39 42 ), including studies from Norway ( 39 , 40 ). Overall, our study did not contribute to clarify the relationship between alcohol consumption and sick leave.…”
Section: Discussionsupporting
confidence: 93%
“…In some cases, there were differences in the measurement of alcohol consumption (e.g., average weekly volume, or alcohol use disorder) ( 28 , 40 ). Moreover, although our results were consistent with some Norwegian studies ( 39 , 40 ), those results were focused on individual-level factors and not company-level determinants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, between-country variation in sickness absence including benefits and often how the social health protection (SOCPRO) systems in each country are organized may influence the type and duration of sickness absence [ 42 ]. For instance, comparing two included Nordic countries, the likelihood of sickness absence was significantly higher for all studies conducted in Norway [ 90 , 93 , 95 , 98 , 102 , 107 , 108 ], compared to studies from Denmark [ 61 , 62 , 86 ]. These rates might be affected by the existing sickness absence benefit systems in each country.…”
Section: Discussionmentioning
confidence: 99%
“…However, while looking into the association between tobacco use and binge drinking, it was found that those who used tobacco were more likely to experience binge drinking than those who did not use it. A Norwegian study [40] reported that smoking or tobacco use was associated with alcohol use, particularly among men. Conversely, a study in Namibia [41] reported that both males and females who used tobacco were associated with alcohol use behaviors, but females had greater odds than males.…”
Section: Discussionmentioning
confidence: 99%